Changes in volume, clinical practice and outcome after reorganisation of oesophago-gastric cancer care in England: A longitudinal observational study. Issue 4 (April 2018) - Varagunam, M.; Hardwick, R.; Riley, S.; Chadwick, G.; Cromwell, D.A.; Groene, O.
Abstract: Aim: The centralisation of oesophago-gastric (O-G) cancer services in England was recommended in 2001, partly because of evidence for a volume-outcome effect for patients having surgery. This study investigated the changes in surgical services for O-G cancer and postoperative mortality since centralisation. Methods: Patients with O-G cancer who had an oesophageal or gastric resection between April 2003 and March 2014 were identified in the national Hospital Episodes Statistics database. We derived information on the number of NHS trusts performing surgery, their surgical volume, and the number of consultants operating. Postoperative mortality was measured at 30 days, 90 days and 1 year. Logistic regression was used to examine how surgical outcomes were related to patient characteristics and organisational variables. Results: During this period, 29 205 patients underwent an oesophagectomy or gastrectomy. The number of NHS trusts performing surgery decreased from 113 in 2003–04 to 43 in 2013–14, and the median annual surgical volume in NHS trusts rose from 21 to 55 patients. The annual 30 day, 90 day and 1 year mortality decreased from 7.4%, 11.3% and 29.7% in 2003–04 to 2.5%, 4.6% and 19.8% in 2013–14, respectively. There was no evidence that high-risk patients were not undergoing surgery. Changes in NHS trust volume explained only a small proportion of the observed fall in mortality. Conclusion: Centralisation of surgical services for O-G cancer in England has resulted in lower postoperative mortality. This cannot be explained by increased volume alone.